PERBANDINGAN PEMAHAMAN KONSEP FISIKA DASAR BERDASARKAN JALUR MASUK PROGRAM STUDI PENDIDIKAN FISIKA FAKULTAS TARBIYAH DAN KEGURUAN UIN ALAUDDIN MAKASSAR - Jusriana, Andi; Sulastri, Sri; Astuti , Nurwidya (JPF (Jurnal Pendidikan Fisika) Universitas Islam Negeri Alauddin Makassar, 2022)
The purpose of this study was to compare the understanding of basic physics concepts I batch 2020 based on the entry path to the physics education study program of the tarbiyah faculty and teacher at UIN Alauddin Makassar. The sample used in this study was a saturated sample, namely all 67 students of physics education class of 2020, totaling 67 people. The data collection instrument used was 10 essay questions on understanding basic physics concepts I, with descriptive statistical data analysis techniques and inferential statistics, namely the one way ANOVA test. Based on the results of data analysis using descriptive statistics, the results of the SPAN entry route were in the medium category, the UMPTKIN entry route was in the low category and the UMM entry route was in the medium category. Furthermore, for the inferential statistics between the SPAN entry route between UMPTKIN, the UMPTKIN entry route between UMM and the UMM entry route between SPAN, there is a difference in understanding of the basic physics concept I batch 2020 based on the entry path to the physics education study program, tarbiyah faculty and teacher at UIN Alauddin Makassar. Kata kunci:Pemahaman Konsep; Jalur masuk